Patient Safety Round to Improve Patient Safety Goals in Hospital Inpatient Units - Dwi Saptarini, Swastika; Sujianto, Untung; Nurjazuli, Nurjazuli (Public Health Perspective Journal, 2021)
The patient safety round is one way to improve the patient safety culture. Potential injury, non-injury and adverse events can be prevented by the patient safety rounds. The purpose of this study was to increase patient safety goals with patient safety rounds in inpatient units by nurses. This study is a quasi-experimental design with a pre- and post-test with a control group. The research subjects consisted of 30 control groups and 30 intervention groups. Patient safety achievements are measured by a patient safety checklist. Data analysis used the Mc Nemar test to determine the difference in the achievement of patient safety goals before and after the patient safety round was carried out. The results of data analysis showed that the patient safety round significantly affected the completeness of the achievement of patient safety goals (p=0.000). Monitoring and evaluation of implementation and achievements must be carried out regularly in order to find new breakthroughs to improve the hospital quality in the 4.0 era. With the patient safety rounds, it is hoped that patient safety goals can be achieved and the level of patient safety will be increased.